Pola Dakwah dalam Program Kafilah Du’at Ma’had Aly Baiturrahman Garut - Laila Nazmi Zahrani; Irfan Safrudin; Malki Ahmad Nasir (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. This research discusses the preaching patterns in the Kafilah Du’at program at Ma’had Aly Baiturrahman IAI Persis Garut, focusing on the implementation, the strategy of communication, the supporting and hindering factors. This program aims to spread the Islamic preaching in 3 areas that all frontier, outermost, and disadvantaged regions through a more social, humanistic, and contextual approach. The method used is descriptive qualitative with observation, interviews, and documentation as the data collection techniques. The data were obtained from Kafilah Du’at members, local communities, and program organizers. The results show that the preaching patterns applied are adaptive through social communication approaches based on ethics and courteous communication, supported by religious studies activities and community empowerment. The main obstacles include the limited facilities and the community’s low which are understanding of religion, while the supporting factors are well-structured personnel development and strong institutional support. This program has proven effective in building emotional connections and gradually increasing religious understanding among the community. Abstrak. Penelitian ini membahas pola dakwah dalam program Kafilah Du’at di Ma’had Aly Baiturrahman IAI Persis Garut, dengan fokus pada bagaimana pelaksanaan, pola dakwah yang digunakan, serta faktor pendukung dan penghambatnya. Program ini bertujuan menyebarkan dakwah ke daerah 3T dengan pendekatan yang lebih sosial, humanis, dan kontekstual. Metode yang digunakan yaitu deskriptif kualitatif dengan teknik observasi, wawancara, dan dokumentasi. Data diperoleh dari anggota Kafilah Du’at, masyarakat setempat, dan pengelola program. Hasil penelitian menunjukkan bahwa pola dakwah yang diterapkan bersifat adaptif melalui pola pendekatan komunikasi sosial berbasis adab dan komunikasi santun, didukung dengan kegiatan kajian agama dan pemberdayaan masyarakat. Hambatan utama meliputi keterbatasan fasilitas dan pemahaman agama masyarakat yang masih minim, sementara faktor pendukungnya adalah pembinaan kader yang terstruktur dan dukungan lembaga yang kuat. Program ini terbukti mampu membangun kedekatan emosional dan meningkatkan pemahaman keagamaan masyarakat secara bertahap.